Игнаш сайкемын: роман / Римма Игнатьева - Игнатьева Римма Серафимовна (Удмуртия, 2020)
Экземпляры: СБ (20200921) / Инвентарный номер: 59684 / Цена: 600.00 / Сис.шифр: С(удм) / Авт.знак: И 26 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)